Effect of High Myopia and Cataract Surgery on the Correlation Between Diabetic Retinopathy and Chronic Kidney Disease - Kong, Huiqian; Zang, Siwen; Hu, Yijun; Lin, Zhanjie; Liu, Baoyi; Zeng, Xiaomin; Xiao, Yu; Du, Zijing; Guanrong, Wu; Ren, Yun; Fang, Ying; Xiaohong, Yang; et al. (Frontiers in Medicine, 2022)
Purpose. To investigate the effect of high myopia and cataract surgery on the progression of diabetic retinopathy (DR) and their roles in the correlation between DR and chronic kidney disease (CKD). Methods. A total of 1063 eyes of 1063 diabetic patients were enrolled. We conducted binary and multiple multivariate regressions to analyze the ocular and systemic risk factors of DR. Based on the presence of myopia and history of cataract surgery, we divided the cases into four subgroups, namely those with high myopia, with cataract surgery, with both conditions, and with neither, then determined the correlation between the stages of DR and CKD. Results. In the binary analysis, high myopia was identified as the protective factor for DR (odds ratio (OR): 0.312 (95% confidence interval (CI): 0.195–0.500, p<0.001), whereas cataract surgery was one of the independent risk factors for DR (OR: 2.818 (95% CI: 1.507–5.273), p=0.001). With the progression of DR, high myopia played an increasingly protective role (mild non-proliferative DR (NPDR), OR=0.461, p=0.004; moderate NPDR OR=0.217, p=0.003; severe NPDR, OR=0.221, p=0.008; proliferative DR (PDR), OR=0.125, p=0.001), whereas cataract surgery became a stronger risk factor, especially in PDR (mild NPDR, OR=1.595, p=0.259; moderate NPDR, OR=3.955, p=0.005; severe NPDR, OR=6.836, p＜0.001; PDR, OR=9.756, p＜0.001). The correlation between the stages of DR and CKD in the group with neither high myopia nor Cataract surgery was the highest among subgroups. Conclusion. High myopia is a protective factor, whereas cataract surgery is a risk factor for DR, and both factors showed tendencies of stronger effects during the progression of DR. The stages of DR and CKD showed a higher correlation after adjustment of the ocular confounding factors.